A Dynamic Perspective on Minimum Quality Standards under Cournot Competition - Stefan Napel; Gunnar Oldehaver (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2009)
Imposing a minimum quality standard (MQS) is conventionally regarded as harmful if firms compete in quantities. This, however, ignores its possible dynamic effects. We show that an MQS can hinder collusion, resulting in dynamic welfare gains that reduce and may outweigh the static losses which are caused by regulation's distortive effect on equilibrium qualities. Verdicts on MQS thus depend even more on the market structure at hand than has been acknowledged.
Keywords: L41; L51; L15; D43; 330; Minimal quality standard; Cournot competition; collusion; Produktqualität; Normung; Nichtpreiswettbewerb; Kartell; Theorie